Sacral Heritage of the Carpathian Region and Management of its Resource Component in Tourism Activity - Iryna, Dobynda; Hyshchuk, Roman; Krool, Volodymyr; Vdovichen, Anatolii (Oles Gonchar Dnipro National University, 2021)
The Carpathian Recreation/Tourism Region (hereafter – CRTR) in Ukraine is a unique territory featuring the sacral historic-cultural heritage of different-time periods beginning from Ancient Rus, Lithuanian, Ottoman, Austro-Hungarian and until Polish, Ro manian, Czech and Ukrainian times. This is why it seems urgently necessary to assess in as much detail as possible the sacral historic-cultural heritage (hereafter – HCH) of the Carpathian Recreation/Tourism Region in Ukraine and provide for the mechanisms of management of the same so that the aforementioned heritage will be as quickly and intensely as possible involved into a common cultural and tourism space and trans-border cooperation with neighboring EU countries, that is, Ro mania, Slovakia, Poland, Hungary and Moldova. For this purpose different types of conservation status (e.g., UNESCO and national heritage) were considered and spatial differences in the sacral historic-cultural monuments (hereafter – HCM) were analyzed through the assessment of their number, modified indices of the sacral objects’ concentration, coefficients of localization and educational value, etc, with application of the methods of partial and integral point-based ranking and cluster analysis with respect to the 58 administrative districts of the region. Following the survey of the CRTR where the sacral HCM were found to be the range from average to very good condition , and proceeding from ethnographic-historical context, the region was spatially differentiated into the Roztotsko-Boykivskyy Meso-District on the northwest, the Hutsul Meso-District in the Prykarpattia, and the Bukovynian Ukrainian-speaking and Romanian speaking micro-districts in the Prypruttia. Among the 6 formed district-status CRTR clusters, 3 of them (27.6% of the administrative districts of the region) were assessed as the most optimal for the purpose of efficient tourism/excursion activity (hereafter - TEA) and its management, while average geometric indices of all aforesaid coefficients ranged from the above-average (4.10) to the highest (7.59) throughout the whole region. It is suggested to achieve efficient tourism management within the studied territories by way of more active introduction of a series of previously tested pilgrimages and educative-religious tours, as well as through different interstate events of trans-border cooperation. All these would increase the competitiveness of the HCM-oriented tourism industry, be helpful in ascertaining which specifically attractive territories should receive investment, and help integrate the Carpathian Region of Ukraine into the common cultural and tourism space of the EU countries.
Keywords: sacral heritage, tourism, rating, cluster, destination, Carpathians